Technology policy in the energy sector: issues, scope and options for developing countries (UN New YorkUS, 1989)
Examines the scope and options for action on the transfer of petroleum-prospecting technology; technology policy for the power plant sector; the development and diffusion of renewable energy technologies; and the strengthening of technology capacity for increased energy efficiency.
DC